Identifying Urban Design Principles and its Attributes for Waterfront Transit-oriented Development (Wtod) - Nabilah Redzuan; Noorhayati Ismail; Norsidah Ujang; Nurul Syala Abdul Latip (Malaysia institute of planner, 2024)
Indexed by Scopus/MyCite